Design of a modified AFM setup with miniaturized - magnetic particle actuators for biomolecular applications - Sevim, Semih. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
In this thesis, design and characterization of a new atomic force microscopy (AFM) setup having conventional piezoactuator together with an electromagnetic actuator and a novel AFM technique using miniaturized-magnetic particles as an actuator for biomolecular experiments are presented. Jetted-polymers have been used in the mechanical assembly of AFM head, which allows rapid manufacturing. A PXI (Peripheral Component Interconnect, PCI extensions for Instrumentation) embedded controller programmed in NILabVIEW environment is used to drive the system. An integrated force resolution of 2 and 3 pN, respectively in air and in liquid is achieved in 1 kHz bandwidth with commercial cantilevers. In addition, a FeCo-tipped electromagnet provides high-force cantilever actuation with vertical magnetic fields up to 0.55 T. Temperature stabilization within 0.1° C is achieved using a Peltier cooler (TEC) to avoid the temperature increase due to the Joule heating of coil. Single-molecule experiments have been conducted using two different pairs of biomolecules (i.e. biotin/streptavidin and heparin/FGF-2). Both biomolecular pairs have been probed using conventional techniques (i.e. piezoactuation or electromagnetic actuation) on both commercial and new custom AFM system. In addition, a novel AFM technique is presented by manipulating functionalized magnetic microbeads using an electromagnet against a stationary AFM cantilever for advanced single-molecule force spectroscopy experiments. This method leads to a significant reduction of mechanical drift in the system since the experiments are performed without a need for a hard surface and the measured force between the cantilever and the bead is inherently differential. In addition, shrinking the size of the actuator can minimize hydrodynamic forces affecting the AFM cantilever. The new method reported herein allows applying constant force on the beads to perform force-clamp experiments without any active feedback. v
Keywords: Atomic force microscopy.